Stress Response of Vibrio parahaemolyticus and Listeria monocytogenes Biofilms to Different Modified Atmospheres - Qian, Hui; Li, Wei; Guo, Linxia; Tan, Ling; Liu, Haiquan; Wang, Jingjing; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2020)
The sessile biofilms of Vibrio parahaemolyticus and Listeria monocytogenes have increasingly become a critical threat in seafood safety. This study aimed to evaluate the effects of modified atmospheres on the formation ability of V. parahaemolyticus and L. monocytogenes biofilms. The stress responses of bacterial biofilm formation to modified atmospheres including anaerobiosis (20% carbon dioxide, 80% nitrogen), micro-aerobiosis (20% oxygen, 80% nitrogen), and aerobiosis (60% oxygen, 40% nitrogen) were illuminated by determining the live cells, chemical composition analysis, textural parameter changes, expression of regulatory genes, etc. Results showed that the biofilm formation ability of V. parahaemolyticus was efficiently decreased, supported by the fact that the modified atmospheres significantly reduced the key chemical composition [extracellular DNA (eDNA) and extracellular proteins] of the extracellular polymeric substance (EPS) and negatively altered the textural parameters (biovolume, thickness, and bio-roughness) of biofilms during the physiological conversion from anaerobiosis to aerobiosis, while the modified atmosphere treatment increased the key chemical composition of EPS and the textural parameters of L. monocytogenes biofilms from anaerobiosis to aerobiosis. Meanwhile, the expression of biofilm formation genes (luxS, aphA, mshA, oxyR, and opaR), EPS production genes (cpsA, cpsC, and cpsR), and virulence genes (vopS, vopD1, vcrD1, vopP2β, and vcrD2β) of V. parahaemolyticus was downregulated. For the L. monocytogenes cells, the expression of biofilm formation genes (flgA, flgU, and degU), EPS production genes (Imo2554, Imo2504, inlA, rmlB), and virulence genes (vopS, vopD1, vcrD1, vopP2β, and vcrD2β) was upregulated during the physiological conversion. All these results indicated that the modified atmospheres possessed significantly different regulation on the biofilm formation of Gram-negative V. parahaemolyticus and Gram-positive L. monocytogenes, which will provide a novel insight to unlock the efficient control of Gram-negative and Gram-positive bacteria in modified-atmosphere packaged food.